Analisis Persepsi Produk Tembakau Alternatif PT XYZ: Studi Perilaku Konsumen Perokok Dewasa di Indonesia - Eling Anindita, Raden; Nadlifatin, Reny; Ratnasari, Vita (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
To face the challenges of changing business landscapes in the cigarette industry driven by regulations and shifting consumer behavior trends, PT XZY launched alternative tobacco product innovations. This research intends to analyze the understanding of adult smokers and the factors that influence their behavior in switching from conventional cigarettes to alternative tobacco products as new products where market characteristics have not yet been identified academically in Indonesia. The research was carried out using a qualitative approach through field observations, document analysis and in-depth interviews (phenomenology). Research identifies that in the product aspect, consumers appreciate the superiority of hygiene (free of smoke, ash and odor) and lower risk compared to conventional cigarettes (although not completely risk free) which is influenced by the nicotine extraction mechanism in tobacco by heating rather than burning. However, users still emphasize the different taste and experience compared to conventional cigarettes (especially kretek). Several main factors that influence the switch from conventional cigarettes to alternative products are emotional benefits (customer engagement), financial (price of devices and tobacco sticks), marketing campaigns (through WoM and media), human resources (product experts) and hygienic products. Then there are social environmental factors (family and community encouragement), availability (distribution) and the existence of official kiosks which are managed directly by the company (sales channels). Marketing strategy design needs to emphasize expanding customer advice or advocacy (positive conversations) and human aspects (human centric), including personalization of information, interaction and total immersion (omnichannel). Marketing should be oriented towards customer behavior aimed at humanizing the brand with human-like attributes with appropriate marketing metrics and the widest use of digital technology.